ANALISIS PROFESIONALISME KERJA PEGAWAI DALAM PELAYANAN PUBLIK DI KANTOR CAMAT GUNUNGSITOLI IDANOI - SEPRIMAN LAOLI; EKA SEPTIANTI LAOLI; NETTI KARIANI MENDROFA (JURNAL ILMIAH SIMANTEK, 2022)
Regional autonomy encourages the central government to issue various laws and regulations to regulate relations in the field of employment. In the current era of globalization, one of the biggest challenges faced by the government in Indonesia, especially local governments is how to present government officials who are professional, have a high category work ethic, competitive advantage, the ability to adhere to bureaucratic ethics in carrying out work assignments. and its functions, and fulfill the aspirations of the people to be free from collusion, corruption, and nepotism. Professionalism is largely determined by the ability of a person or individual in doing a job according to the field of duty and their respective levels. The results of the work are more viewed from all aspects according to the portion, object, are continuous in any situation and condition and the period of completion of the work is relatively short. Through this research, researchers will find out more about how professional the employees work and the quality achieved by employees at the research location.